Virtual reality as a non-pharmacological method to support therapeutic interventions in palliative care patients - Mulawa, Magdalena Maria; Krycia, Kamila; Mazur, Karolina; Różycka, Karolina; Piaszczyńska, Emilia; Gałuszka, Aleksandra; Matacz, Dominika; Drabik, Sandra; Gałuszka, Maja; Adamczyk, Adrianna (Journal of Education, Health and Sport, 2026)
Aim: The aim of this study is to review the existing literature and research on the application of virtual reality technology in palliative care, with particular emphasis on its impact on pain intensity, psychological well-being, patients’ quality of life, as well as an analysis of its feasibility and safety. Materials and Methods: The literature was searched using the PubMed, Google Scholar, and Scopus databases (2013–2026). The following keywords were used: “virtual reality”, “palliative care”, “hospice care”, “end of life”, “pain”, “quality of life”, and “anxiety”. Results: The available evidence suggests that virtual reality represents a viable therapeutic option, generally not associated with significant adverse effects. Studies indicate a short-term reduction in perceived pain, a potential decrease in anxiety levels, and an improvement in psychological well-being. The effectiveness of the intervention depends, among other factors, on the type of content presented, such as nature-based imagery or materials tailored to the individual needs of the patient. However, there remains a lack of studies enabling the standardisation of parameters such as session duration and frequency, while the considerable heterogeneity of applied protocols makes comparison of results challenging. Conclusions: Virtual reality (VR) may constitute a valuable adjunct to standard palliative care in the management of symptoms and provision of psychological support, particularly as a short-term intervention in hospital and hospice settings. Further randomised clinical trials are warranted, alongside the development of guidelines for the implementation of VR in palliative care practice.